The stone in a monumental masonry building of the Tyrrhenian coast (Italy): new data on the relationship between stone properties and structural analysis - Forestieri, Giulia; Tedesco, Alessandro; Ponte, Maurizio (Ge-conservacion, 2017)
In order to assess physical-mechanical properties of building material (“Fuscaldo sandstone”), non-destructive tests have been performed in the main façade of “Palazzo Carelli - Pignatelli” (14th-15th centuries) in Fiumefreddo Bruzio (Italy), situated in the Tyrrhenian Coast (in the South of Italy). Mechanical properties have been assessed through Schmidt hammer hardness and ultrasound velocity tests. Structural analyses have been carried out to assess collapse mechanisms of the entire façade. Results provide a preliminary comprehensive understanding of the decay level and instability of the building.